2023
DOI: 10.1021/acs.analchem.2c05098
|View full text |Cite
|
Sign up to set email alerts
|

A Strategy for the Determination of Alkaline Phosphatase Based on the Self-Triggered Degradation of Metal–Organic Frameworks by Phosphate

Abstract: Alkaline phosphatase (ALP) is widely present in the human body and is an important biomarker. Numerous ALP detection studies have been carried out, and ascorbic acid (AA) is often used as the reducing component in the sensors to monitor ALP levels since it can be produced from ascorbic acid 2-phosphate (AA2P) hydrolysis in the presence of ALP. However, it is well-known that AA is a strong reducing agent and can be easily oxidized. The disproportion between oxidized AA and reduced AA reactions results in the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…It can be easily observed that with the designed primer 24, the highest F/F 0 value was obtained, indicating the best recognition response of OTA and releasing of the primer probe to activate the RCA for signal amplification. Meanwhile, according to the previous report, 40 molecular crowding could boost the aptamer's binding affinity by adding the surfactant to increase the viscosity. Different categories of binding buffers including 0.02% w/v PEG 200, PEG 600, PEG 1000, PEG 6000, PEG 10000, PEG 20000, Tween-20, and Tween-80 were verified as shown in Figure 2D.…”
Section: Resultsmentioning
confidence: 97%
“…It can be easily observed that with the designed primer 24, the highest F/F 0 value was obtained, indicating the best recognition response of OTA and releasing of the primer probe to activate the RCA for signal amplification. Meanwhile, according to the previous report, 40 molecular crowding could boost the aptamer's binding affinity by adding the surfactant to increase the viscosity. Different categories of binding buffers including 0.02% w/v PEG 200, PEG 600, PEG 1000, PEG 6000, PEG 10000, PEG 20000, Tween-20, and Tween-80 were verified as shown in Figure 2D.…”
Section: Resultsmentioning
confidence: 97%
“…Abnormal enzyme activity is associated with numerous diseases, making enzymes valuable biomarkers for effective clinical diagnosis . For example, alkaline phosphatase (ALP) catalyzes hydrolysis and phosphor-transfer reactions of proteins, nucleic acids, and small-molecules orbiomolecules both inside and outside the organism. , Deviations in ALP levels are linked to various disorders, including bone disease, hepatitis, diabetes, prostate cancer, and hepatocellular carcinoma. Therefore, ALP is widely recognized as a critical diagnostic and treatment predictor .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, fluorescence-sensing systems have drawn extensive attention from researchers due to their advantages such as simple operation, less sample consumption and real-time detection. At present, inorganic quantum dots, metal–organic frameworks, coordination polymers and traditional organic dyes have been successfully used in the development of ALP fluorescent sensors [ 16 , 17 , 18 , 19 , 20 , 21 ]. However, the current design of sensing systems still has many defects, such as the complex synthesis and modification process of fluorophores, the high toxicity of inorganic quantum dots and the poor solubility of traditional organic dyes in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%